Increasing Parents' Capacity in Caring for Children with Autism Spectrum Disorder Through Parenting Seminars - Luqyana Dhiya Amira; Rosa Auralia Wulandari; Arum Sekar Kinasih; Novia Nuril Firdaus; Faktian Okta Zulfikar; Ediyanto (Formosa Journal of Sustainable Research, 2023)
This research aims to measure the effectiveness of parenting seminars in improving parents' abilities regarding caring for children with autism. The research method used was the onegroup pretest posttest method. The subjects of this research were all parenting seminar participants, namely parents/guardians of students with autism. To gain insight into parenting patterns by parents, data was collected using survey techniques by filling out questionnaires that were provided before and after the seminar activities. Data analysis uses the gain test. The research results showed that the average pretest score was 68.47. The average posttest score is 90.09. This means that parental insight has increased by 21.62, and the test gain is included in the medium and high categories. Based on these results, parenting seminars can increase parents' insight into parenting autism